The safety situation of the digital hospital and its countermeasures - Wang, Min; Ge, Yi; Deng, Hou-bing; Li, Xiang-jun (Zhongguo yi liao qi xie za zhi, 2006)
This article introduces briefly the content of the disaster backup technology which should be attached same great importance to, as the construction and application of a information system.This article introduces briefly the content of the disaster backup technology which should be attached same great importance to, as the construction and application of a information system.